Effectiveness of an Intervention Program to Improve Compliance with Hand Hygiene among Health Staff in NAFH - Harrabi, Imed; Al-Ghamdi, Saad; Cubelo, Paolo (Journal of Health and Allied Sciences NU, 2017)
Background: Hand Hygiene, either by hand washing or hand disinfection, remains the single most important measure to prevent nosocomal infections.Objective: To increase Hand Hygiene compliance to at least 10% among health care staffs in female and medical wards after six months of a pilot intervention program.Methods: It was a pre-post intervention study in Najran Armed forces Hospital during the year 2015. knowledge was assessed using WHO's hand hygiene questionnaire Measurement of attitude was done on the basis of 13 questions where the subjects had to give their opinion on a 1 to 5 point Liker Scale ranging from strongly disagree to strongly agree. Compliance was measured and directly observed by experienced infection control linkers.Results: the results of our study showed a positive effect of the pilot intervention program on knowledge, attitude and compliance on hand hygiene. An increase in compliance of 6.44% and 7.56% were observed in Female Ward and Male Ward respectively in post-intervention.Conclusions: All should be done to maintain the positive trend of hand hygiene compliance. The infection control team should be encouraged to maintain a continuous monitoring of hand hygiene compliance and have a positive interaction with the health staff.
Keywords: Hand hygiene (HH); Hospital Acquired Infections(HAI); pilot intervention; health staff